Kolokasi Bahasa Inggris dalam Tugas Akhir Mahasiswa: Analisis Berbasis Frekuensi dengan Google sebagai Korpus - Tri Nuraniwati; Ashfa F Lathifah (JLA (Jurnal Lingua Applicata), 2018)
This study aims to analyze the search results’ frequency of collocations used by students of English Program, Vocational College UGM in their graduating papers (Tugas Akhir) and to show how Google can be used as a practical online corpus for collocations query. Collocations are words that co-occur together in any text and have fixed association. The use of collocations is part of linguistic awareness which determines how language is used in its natural state. Through corpus-based analyses, 1000 collocations are randomly chosen from 10 graduating papers (100 collocations per graduating paper). Using Google search engine, each collocation is entered as key words to find out the frequency of its search hits. The frequency is subsequently categorized into high frequency, medium frequency, and low frequency. From the 1000 collocations, 802 (80.2%) collocations belong to high-frequency collocations, 120 (12%) collocations are in the category of medium frequency, and 78 (7.8%) collocations are categorized as low-frequency collocations. The results indicate that students have shown good level of accuracy in using collocations in their academic writing.